The best summer of our lives - Hauck, Rachel, 1960- (Bethany House Publishers, a division of Baker Publishing Group, 2023)
"When Summer's music career crumbles, she returns to the place where secrets, wounds, and fears destroyed her closest friendships. It will take a reckoning with her past and the friends she lost to help her gain the closure she needs to move forward"--